PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TSOS (THREE STAY ONE STRAY) UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS IV PADA MATA PELAJARAN IPA DI SDN KANIGORO 03 KOTA MADIUN - Selly Nurina Suraya (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2011)
The objective of this research is to improve the fourth graders’ social skills in the subject of natural science through applying type of TSOS at the elementary school of SD Kanigooro 03 Madiun. The mothod adopted is qualitative while the design is classroom action research. The research took place at SD 03 Kanigoro 04 for 4 months, i.e. February through Mei 2011. As many as 31 students involved as the subject of this research. Data were collected through observation. It was applied to observe their social skills (affective domain) during the teaching-learning process which covered the skills to share, to participate, and to communicate. An observation sheet was the instrument to collect data during the observation which, then, descriptively analyzed. Results in the first cycle showed their average scores came out of a single social skill. The average of every aspect, respectively,: the skill to share 63.74; that to participate 64.58; and that on communication 59.77. Results in the second cycle indicated a significant increase. They could share, participate and communicate better than before. Their average scores were: 84.67 for the skill to share; 87.09 for that to participate; and 84.67 for that for communication. A conclusion drawn is that the cooperative learning type of TSOS can improve the fourth graders’ social skills of SD Kanigoro 03 Madiun. Their average skill to share improved from 63.74 in the first cycle to 84.67 in the second cycle. That on the participation was from 64.58 to 87.09. Last of all, that on communication was from 59.77 to 84.67.